Assessment of alternative land resource utilisation towards Net-Zero and regional revitalisation through the circulating and ecological sphere in depopulated city regions in Japan: a case study of Hachinohe City Region - Sato, Haruno; Mitra, Bijon Kumer; Dasgupta, Rajarshi; Hashimoto, Shizuka (Sustainability science, 2023)
The circulating and ecological sphere (CES) concept promotes a self-reliant decentralised society by utilising regional resources to achieve decarbonisation. The concept is particularly relevant to depopulated areas across Japan facing a continuous increase of underutilised agricultural land that brings environmental, social and economic challenges. This study recognises such land as a locally available resource to be re-utilised under the CES framework and mitigate issues in a depopulating community. Using the case of the Hachinohe City Region in Japan, this paper explores alternative land-use scenarios and identifies policy interventions to implement a desirable scenario that would contribute to the localisation of Net-Zero and regional revitalisation. The scenarios developed based on land-use change analysis, policy reviews and stakeholder interviews were: (1) an energy-dominant scenario (installing a photovoltaic system) and (2) an agriculture–energy combination scenario (installing an agrivoltaic system). The analysis shows that under both scenarios, Hachinohe City Region can achieve 100% renewable energy. There are other benefits, including job creation and, in the case of the agriculture-solar scenario, contribution to domestic food supply resiliency. The study recommends three policy interventions: (1) collaboration amongst the members of the city region to achieve its own carbon–neutral electricity supply; (2) investment for areas without transmission lines to fully benefit from their regional resources; and (3) support for local initiatives where local communities co-manage the resources and co-benefit from them. Based on the results, the paper further highlights the potential of the CES approach to deliver just transition from a spatial perspective.